PWE-016 Pelvic Radiation Disease – A Comparison Of Reported Symptoms In Oncology And Gastroenterology Clinics. (9th June 2014) - Stacey, R; Abraham, L; Turner, J; Green, J
Abstract : Introduction: Pelvic radiation disease and consequences of cancer treatment are common. Improved cancer survivorship has increased awareness of these problems but it remains under diagnosed, under investigated and under recognised by physicians. Gastrointestinal side effects are common post pelvic radiotherapy and can have significant impact on a patients quality of life. PRD ranges in severity, from mild self limiting disease through to significant and debilitating symptoms with high morbidity. We assessed the late GI side effect symptoms reported to doctors at oncology clinics and compared them to the symptoms reported to doctors at GI clinic (where the most severe cases are investigated) at our centre. Methods: Patients (n = 295) referred to Velindre NHS Trust with gynaecological, colorectal or urological malignancy between 1st Jan and 30th June 2008 were identified through a pelvic radiotherapy database. Patients who had received radiotherapy and/or brachytherapy as radical or adjuvant treatment were included. Patients treated initially with palliative intent and patients treated for recurrent disease were excluded. Patients referred to GI clinic at University Hospital Llandough or the via direct access endoscopy service with suspected PRD are entered on a local database. We identified all patients referred prior to 2013 (n = 34). In both groups we recorded the presenting GI symptoms and the original malignancy and treatment plan. Results: 30.8% of patients seen in oncology clinic experienced late GI side effects post pelvic radiotherapy. Only a small proportion of these were referred to clinic. Of those referred, rectal bleeding and diarrhoea were the predominant symptoms, along with abdominal pain and bloating. Several patients had multiple symptoms. Conclusion: Late GI side effects of pelvic radiotherapy are common, but the number seen in GI clinic are small. PRD varies in severity, but is under referred by oncologists and primary care practitioners, is poorly recognised by Gastroenterologists and often under investigated. Treatment for consequences of cancer therapy exists, and with increased cancer survivorship, focus should be on minimising symptoms, allowing patients to live after cancer, and not merely survive. Disclosure of Interest: None Declared.